Recreational outdoor physical activity and sport participation among ethnic minority children in Finland - Tiermas, Aada (2025)
Physical activity (PA) in childhood is important, and while efforts are made to promote children’s PA, inequality still exists. Ethnic minorities, in particular, are often in a more disadvantaged position and tend to engage in physical activities less than the majority population. With increased immigration multiculturalism has increased, and simultaneously decreased PA of children is a concern globally. This thesis explores recreational outdoor PA and sport participation of ethnic minority children in Finland. It examines how much children engage in PA outside of day care and examines differences across ethnic minority groups as well as between native majority and ethnic minority children. Lack of research exists in Finnish context as well as research on differences across ethnic minority groups and preschool aged children is scarce. This thesis is conducted in collaboration with Diginatiivit-project at the University of Jyväskylä, which is a part of an international research project International ipreschooler Surveillance Study Among Asians and OtheRs (IISSAAR). The IISSAAR research focused on studying digital and non-digital behaviours of preschool children and their adherence to WHO movement guidelines. As a part of IISSAAR, SMALLQ® survey was developed, and the data collected through the questionnaire in Finland is used in this thesis.